2016
DOI: 10.1016/j.energy.2016.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Energy conversion under conjugate conduction, magneto-convection, diffusion and nonlinear radiation over a non-linearly stretching sheet with slip and multiple convective boundary conditions

Abstract: Energy conversion under conjugate conduction, magnetoconvection, diffusion and nonlinear radiation over a nonlinearly stretching sheet with slip and multiple convective boundary conditions Uddin AbstractEnergy conversion under conduction, convection, diffusion and radiation has been studied for MHD free convection heat transfer of a steady laminar boundary-layer flow past a moving permeable non-linearly extrusion stretching sheet. The nonlinear Rosseland thermal radiation flux model, velocity slip, thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…This mobility of microorganisms is simulated by various stimulators such as chemotaxis, photosynthesis, gyrotactic, and so on. Many recent advancements on this topic can be visualized through Kuznetsov et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mobility of microorganisms is simulated by various stimulators such as chemotaxis, photosynthesis, gyrotactic, and so on. Many recent advancements on this topic can be visualized through Kuznetsov et al…”
Section: Introductionmentioning
confidence: 99%
“…This mobility of microorganisms is simulated by various stimulators such as chemotaxis, photosynthesis, gyrotactic, and so on. Many recent advancements on this topic can be visualized through Kuznetsov et al [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Recently, the activation energy has attained the interests of engineers, which was originally proposed by Arrhenius in 1889. This is known as base energy supplied to reactants in chemical processing for the conversion of products.…”
mentioning
confidence: 99%
“…Many researchers have extended the work of Navier . Furthermore, Uddin et al have investigated biconvective electromagnetic nanofluid transport in various geometries considering multiple slip conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the e ect of stretching sheet wall problem adopting natural convective boundary conditions was investigated by Yao et al [23], Kandasamy et al [24], and Makinde and Aziz [25]. More works on parametric studies of the ow process can be found in [26][27][28][29][30][31][32][33][34]. Additionally, analyses of magnetohydrodynamic ow in the porous medium have been presented in various works [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] while various studies of magneto-nano uid ow have also been presented in the past works [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, f 2 (η), θ 2 (η), andϕ 2 (η) are (27), (31), and (35) are solved using the boundary conditions in (28), (32), and (36), respectively. Although the resulting solutions and the other subsequent solutions are too long to be shown in this paper, they are included in the simulated results shown graphically in the results and discussion section.…”
Section: Modelling and Simulation In Engineeringmentioning
confidence: 99%